2019
DOI: 10.1111/psyg.12404
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drug use and favourable natures of emotional functions in patients with dementia

Abstract: Aim To characterise the effects of antipsychotics on brain functions of patients with behavioural psychological symptoms of dementia (BPSD). Methods Studies were performed during 6 weeks of intervention with either a nonantipsychotic drug (group A, n = 38) or an antipsychotic drug (group B, n = 10). Results Neuropsychiatric Inventory scores were significantly decreased in both groups. Scores on the Mini‐Mental State Examination did not change with intervention. By contrast, favourable natures of emotional func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This metric ranged from 0-100, higher scores indicate better performance for ADL. We also used Mini-Mental State Examination (MMSE) (Folstein et al 1975), which ranges from 0-30, higher scores indicate better performance for cognitive function, Neuropsychiatric Inventory (NPI) (Cummings et al 1994) ranged 0-108, lower scores indicate better performance for BPSD, and Delightful Emotional Index (DEI) (Fujii et al 2019) ranged 0-90, higher scores for better performance for favorable emotions at baseline and three months after hospitalization. Patients with MMSE scores ≦ 10 points at baseline were not included for the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This metric ranged from 0-100, higher scores indicate better performance for ADL. We also used Mini-Mental State Examination (MMSE) (Folstein et al 1975), which ranges from 0-30, higher scores indicate better performance for cognitive function, Neuropsychiatric Inventory (NPI) (Cummings et al 1994) ranged 0-108, lower scores indicate better performance for BPSD, and Delightful Emotional Index (DEI) (Fujii et al 2019) ranged 0-90, higher scores for better performance for favorable emotions at baseline and three months after hospitalization. Patients with MMSE scores ≦ 10 points at baseline were not included for the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Dementia patients may exhibit behavior such as agitation, anger, and aberrant motor activity that challenges caregivers, leading to caregiver burden and subsequent placement in a nursing home or a psychiatric hospital for patients with dementia in severe cases. We have suggested that favorable positive emotions should be an important goal for the treatment of negative emotions of behavioral psychological symptoms of dementia (BPSD) (Fujii et al 2019). In contrast to negative emotional status of BPSD, positive emotional status such as exchanging greetings appropriately, exhibiting facial expressiveness, showing interested in something, carrying on a conversation, and showing delight in something are defined as favorable emotions, which is assessed with the Delightful Emotional Index (DEI) (Fujii et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How to cite this article: Fukushima K, Aita E, Butler JP, 1,2 There are several factors responsible for increased ER visits, including lack of knowledge about the complexity of a patient's medical requirements and limited resources for the coordination of transition of care. 3 These factors can lead to disjointed care for the elderly and suggest opportunities for improvement.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Dear Editor, We have suggested that favorable emotions should be cared for in the treatment of behavioral and psychological symptoms of dementia (BPSD). 1 The Internet of Things (IOT) 2 in which multiple programs, devices and algorithms can interact via the cloud and emergent behaviors of complex interconnected systems arise, has been developed. It is speculated whether emotional therapy using IOT in patients with BPSD might be a way to respond to the complex needs of patients, particularly focusing on favorable emotions.…”
mentioning
confidence: 99%